EKSEKUSI BARANG SITAAN BERUPA ASET TIDAK BERGERAK HASIL TINDAK PIDANA KORUPSI - Yogi Nugraha Setiawan; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2022)
The return of assets resulting from corruption has occupied an important position in eradicating corruption, so the success of eradicating corruption is not only measured by the success of punishment, but is also determined by the success rate of restoring state assets that have been corrupted. To find out the execution of confiscated goods in the form of immovable assets resulting from corruption, it is necessary to examine the authority of the prosecutor in carrying out the execution of confiscated goods in the form of immovable assets resulting from criminal acts of corruption, and the implementation of the prosecutor's authority in carrying out the execution of confiscated goods in the form of immovable assets resulting from criminal acts. corruption, as well as the obstacles faced in carrying out the execution of confiscated goods in the form of immovable assets resulting from criminal acts of corruption. It is known that the prosecutor's authority in carrying out the execution of immovable assets resulting from corruption is contained in Article 18 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning the Eradication of Criminal Acts of Corruption. and the implementation of the prosecutor's authority in carrying out the execution of confiscated immovable assets resulting from corruption based on the provisions of PERJA No.013/A/JA/06/2014 concerning Asset Recovery Guidelines, confiscation of assets of perpetrators of corruption is an anticipatory step aimed at saving or preventing the escape of assets Country. The obstacles faced in carrying out the execution of confiscated assets resulting from corruption by the Prosecutor are the lack of instruments in efforts to confiscate assets resulting from criminal acts, and the systems and mechanisms in the seizure of assets from criminal acts have not been able to fully support law enforcement efforts